Filtration markers and determination methods for the assessment of kidney function - Huang, Jiaguo; Gretz, Norbert; Weinfurter, Stefanie (European journal of pharmacology, 2016)
Estimation of renal function is crucial for a number of clinical situations. Endogenous markers such as creatinine, as well as several exogenous agents including inulin, 99mTc-DTPA and iothalamate are used for evaluation of kidney function. At present, new generation filtration markers and determination methods based on organic fluorescent dyes and fluorescent detection technique are developed. This review gives an overview of filtration markers and clearance methods for the assessment of kidney function. New filtration markers and transcutaneous measurement of renal function are described. Problems and issues relating to the reabsorption or secretion of each of markers and the applicability of methods are also discussed.
Gesehen am 28.05.2019
Available online 1 July 2016